United States-China-India strategic triangle in the Indian Ocean Region (KW Publishers General Sir John Kotelawala Defence University, Sri Lanka, 2015)
While the strategic dynamics in the IOR are complex and involve many powers there is little doubt that the "strategic triangle" involving the US, China and India is one of the key traditional security issues facing the IOR. Given Sri Lanka's geopolitically significant location in the IOR this strategic triangle is bound to have an impact on its national interests and security